Determinants Of Human Development Index In Papua Province 2012-2021 - Waridatul Afalia; Ikrima Hamda; Shella Aurelia Adriana; Ahmad Fahrudin Alamsyah; Novi Lailiyul Wafiroh (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
The Human Development Index (HDI) aims to emphasize that a country's development assessment should be based on the capabilities of its population. Papua, as the province with the lowest HDI in Indonesia, reflects the poor level of living and human development in Papua. Although Papua is a special autonomous region that receives an allocation of funds, its public services and people's welfare still lag behind other provinces in Indonesia. The purpose of this study is to understand how Special Autonomy Funds, Sharia Financing, Information and Communication Technology (ICT), and Average Length of School (ALS) affect the Human Development Index. This study uses Error Correction Model (ECM) as an analysis method. The results showed that ICT did not have a significant effect on HDI, Special Autonomy Fund had a negative influence in the short term and a positive influence in the long term, Average School Year had a positive influence in the short term and a negative influence in the long term, while Islamic Bank Financing had a positive influence both in the short and long term.